Short-course neoadjuvant chemoradiotherapy and surgery are beneficial in Chinese patients: A retrospective study. Issue 51 (December 2017) - Huang, Ming Jun; Wang, Xiao Dong; Hu, Yan Jie; Yang, Jie; Li, Ka
Abstract : Abstract: Preoperative neoadjuvant chemoradiotherapy (NACR) is used to reduce tumor size for easier resection or improved resectability rates. Considering the difficulties regarding health insurance and health resources in China, an evidence-based short-course neoadjuvant chemoradiotherapy with surgery to cure patients was performed. This study compared the postoperative effects between short-course neoadjuvant chemoradiotherapy and surgery and surgery without neoadjuvant chemoradiotherapy. The current retrospective study was based on a rectal cancer database, including 274 patients diagnosed with rectal cancer between January 2014 and October 2016. Data were analyzed with respect to curative rate, postoperative recovery indicators (times to nasogastric tube, urinary catheter, and drainage tube removal and times to first oral feeding and passing of flatus postsurgery), chemoradiotherapy-related indicators [white blood cell count (WBC) and carcinoembryonic antigen (CEA) levels], and adverse effects indicators, evaluated according to Common Terminology Criteria for Adverse Events Version 4.0. There was no significant difference between the combined therapy and surgery groups ( P  > .05) in terms of radical resection rates and the times to urinary catheter removal and passing flatus ( P  > .05). Statistically significant differences ( P  < .05) in terms of earlier time for removal of the nasogastric and drainage tubes and time to first oral feeding were observed in the combined therapy group. The decreases in WBC and CEA levels in the combined therapy group were significantly greater than those in the surgery group 1 week after surgery ( P  < .05); after 1 month, the CEA decrease in the combined therapy group was significantly greater than that in the surgery group ( P  < .05). More patients in the combined therapy group experienced vomiting, indigestion, dehydration, oral mucositis, sensory neuritis, and alopecia compared with those in the surgery group 1 week after surgery ( P  < .05); after 1 month, only the incidence of alopecia was higher in the combined therapy group ( P  < .05). The combined therapy group demonstrated earlier postoperative recovery compared with the surgery group. Short-course neoadjuvant chemoradiotherapy with surgery may lead to postoperative treatment-related adverse effects of varying degrees; however, these adverse effects eventually improve with time. Abstract : Supplemental Digital Content is available in the text